Student psychology-based optimization-tuned cascaded controller for frequency regulation of a microgrid - Gupta, Sindhura; Mukhopadhyay, Susovan; Banerji, Ambarnath; Sanki, Prasun; Sinha, Pampa; Biswas, Sujit K.; Khan, Baseem; Ali, Ahmed; Bokoro, Pitshou (Frontiers in Energy Research, 2024)
This paper presents a student psychology-based optimization-tuned cascaded control scheme for an interconnected microgrid scenario. Generally, the different distributed energy sources are assembled to form the microgrid architecture and the majority of the sources are environment-dependent. Further, the intermittent power output from these sources causes a generations-load power mismatch, resulting in power and frequency oscillations. In this regard, the proposed student psychology-based optimization tuned cascaded controller tackles the power-frequency mismatch issues under an interconnected microgrid scenario. Additionally, an improved power tie-line model is introduced considering the effect of line resistance in the microgrid scenario as the line resistance plays a significant role in power flow between the control areas. Besides, numerous case studies are investigated to examine the effectiveness of the proposed design methodology under the suggested control scheme. Furthermore, a detailed performance analysis is carried out considering the proposed model operation under a 12-node radial distribution network in order to examine the system compatibility in a practical distribution network. The obtained results ensure superior performances in terms of the system's overall peak over/undershoots, oscillations, and settling time utilizing the proposed controller under the improved microgrid scenario.